DEVELOPMENT OF AN INTERACTIVE MULTIMEDIA-BASED WEBSITE SUPPORTED BY INTERACTIVE POWERPOINT (POPIN) FOR ELEMENTARY STUDENTS - Winarto, Aprilian Purnomo Hadi; Zaman, Wahid Ibnu; Basori, Muhamad (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study was motivated by observations at SDN Sukorame 2 Kediri, which showed low student learning outcomes in the subject of changes in the form of matter and minimal use of interesting and interactive learning media. These conditions had an impact on low student enthusiasm and understanding in learning. This study aims to develop interactive multimedia based on a website using Interactive PowerPoint (Popin) on the subject of changes in the form of matter in the 4th grade IPAS subject at SDN Sukorame 2 Kediri. The research method used is R&D with the 4D model (Define, Design, Development, and Disseminate). The research instruments include a questionnaire for expert validation of material and media, a questionnaire on practicality for teachers and students, and an effectiveness test. Data analysis is used to determine the level of validity, practicality, and effectiveness of the product. The results of the study show that the interactive multimedia developed was considered highly valid by media experts 93% and subject matter experts 89.1%. The practicality test was considered very practical with a score of 87.4% from teachers and 100% from students. The effectiveness test was considered effective based on classical learning completeness reaching 76%. The novelty of this research lies in the integration of Interactive PowerPoint (Popin) into a website platform so that the media can be accessed without additional applications and provides a more dynamic and flexible learning experience for students. These findings contribute to the development of learning technology that is easy for educators to use but still effective in improving conceptual understanding.